ATMOSPHERIC ELECTRIC FIELD EFFECTS OF COSMIC RAYS DETECTED IN MEXICO CITY - González L.X.; Valdés-Galicia J.F. (My University, 2006)
We studied the possible effects of atmospheric electric fields, generated in thunderstorms, on the cosmic ray intensity detected at the Earth's surface by investigating the variations of the counting rates of the cosmic-ray nucleonic component, obtained from the neutron monitor installed in Mexico City, for thunderstorms during 1996 and 1997. These were years of minimum solar activity. We compare our experimental results with the general theory of cosmic ray meteorological effects by Dorman (1995). The observed intensity variation is about 0.2%. According to Dorman (1995), the effect should be between 0.27% and 0.81% on the counting rate of the neutron monitor when the atmospheric electric field intensities are around 100 to 300 Vcm-1. Our results show that either the electric field in Mexico City had less intensity than assumed by Dorman (1995), or the electric field is not uniform in time and height during the development of the thunderstorm.
Keywords: ATMOSPHERIC ELECTRIC FIELD; COSMIC RAYS